2023
DOI: 10.21037/jtd-22-819
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laparoscopic vs. robotic paraesophageal hernia repair: a systematic review

Abstract: Background: In both clinical practice and residency training, the use of robotic platforms in surgery is becoming more common. The aim of this study was to perform a systematic review of the perioperative outcomes of robotic and laparoscopic paraesophageal hernia (PEH) repair. Methods:The PRISMA statement guidelines were used to perform this systematic review. We conducted a database search which included Ovid MEDLINE(R) and Epub Ahead of Print, In-Process & Other Non-Indexed Citations, and Daily, Ovid EMBASE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 23 publications
1
2
0
1
Order By: Relevance
“…Several large hernia repair trials comparing robotics with laparoscopy, including the RIVAL trial at both 1 and 2 year follow-up as well as ventral hernia repair trials [ [3] , [4] , [5] , [6] , [7] ] have demonstrated equivalent clinical outcomes with added healthcare costs. The findings were similar in studies examining the use of robotics in bariatric surgery [ [8] , [9] , [10] , [11] ], foregut surgery [ 12 ], and colorectal surgery [ [13] , [14] , [15] , [16] ], with one recent study demonstrating increased risk of common bile duct injury during robotic cholecystectomy and questioning the safety of the robotic platform in this surgery [ 17 ]–a procedure increasingly performed using the robot. And, while these studies have focused on the clinical impact of robotics, other studies have demonstrated greater CO 2 emissions and worse environmental impact of robotic surgery when compared with laparoscopy [ 18 , 19 ].…”
supporting
confidence: 69%
“…Several large hernia repair trials comparing robotics with laparoscopy, including the RIVAL trial at both 1 and 2 year follow-up as well as ventral hernia repair trials [ [3] , [4] , [5] , [6] , [7] ] have demonstrated equivalent clinical outcomes with added healthcare costs. The findings were similar in studies examining the use of robotics in bariatric surgery [ [8] , [9] , [10] , [11] ], foregut surgery [ 12 ], and colorectal surgery [ [13] , [14] , [15] , [16] ], with one recent study demonstrating increased risk of common bile duct injury during robotic cholecystectomy and questioning the safety of the robotic platform in this surgery [ 17 ]–a procedure increasingly performed using the robot. And, while these studies have focused on the clinical impact of robotics, other studies have demonstrated greater CO 2 emissions and worse environmental impact of robotic surgery when compared with laparoscopy [ 18 , 19 ].…”
supporting
confidence: 69%
“…Reported operation time varies widely among different centers, although most studies present a signi cant decline as the learning curve grows. [30][31][32] Regarding postoperative symptom relief and quality of life, comparative studies indicated no statistically signi cant superiority for the robotic approach over the laparoscopic. [33][34][35][36][37] Functional examinations have been utilized in a number of prospective studies comparing laparoscopic to robotic approach.…”
Section: Discussionmentioning
confidence: 97%
“…[24] Data on robot-assisted hiatal hernia repair also show excellent results regarding safety and perioperative outcomes even in technically demanding cases [25][26][27][28]. Results regarding postoperative complications are currently inconclusive, as certain studies comparing the laparoscopic and robotic approaches for hiatal hernia repair present dominance of the robotic approach, while others report increased incidence of respiratory complications in patients who undergo robotic repair [29,30]. Reported operation time varies widely among different centers, although most studies present a signi cant decline as the learning curve grows.…”
Section: Discussionmentioning
confidence: 99%
“…A fisiopatologia da HH é baseada principalmente no gradiente de pressão transdiafragmático, no qual sofre ações de pressões positivas, advindo da cavidade abdominal e negativas, oriundas da cavidade torácica, resultando em uma força contínua para cima na JGE. Dessa forma, há violação do hiato esofágico através das diferenças de pressão entre as cavidades torácicas e abdominais, ocasionando o surgimento da HH (HÅKANSON et al, 2018;PETROV et al, 2019;SATHASIVAM et al, 2019;BHATT;WEI, 2023).…”
Section: Definição E Fisiopatologiaunclassified